COMPARATIVE ANALYSIS OF DRUG COSTS BASED ON THE ACTIVITY-BASED COSTING METHOD AND DRUG PRICE RATES, INCLUDING THE EVALUATION OF COST DIFFERENCES AND MANAGERIAL IMPLICATIONS IN THE PHARMACY UNIT OF MARTHA FRISKA MULTATULI HOSPITAL - Ramadhan Diansyah Putra; Erlina; Ibnu Austrindanney Sina Azhar (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the difference between drug Unit Cost calculated using Activity-Based Costing (ABC) and Traditional Unit Cost, and to evaluate its implications for actual margin and tariff policy in the Pharmacy Unit of Martha Friska Multatuli Hospital. A quantitative approach with a descriptive-comparative design was applied. The data were secondary data for the year 2025, comprising drug purchasing records, sales records, selling prices, transaction volume, receipt frequency, and the indirect costs of the pharmacy unit. The sample consisted of 100 drug items with the highest sales volume and complete data, selected through purposive sampling. The results show that the mean ABC Unit Cost was IDR 1,427.62, while the mean Traditional Unit Cost was IDR 1,249.08. The Jarque-Bera normality test indicated that the cost-difference data were not normally distributed, so the Wilcoxon Signed-Rank Test was used and revealed a significant difference between ABC Unit Cost and Traditional Unit Cost (p < 0.001), with a large effect size (r = 0.868). All sampled drugs were undercosted under the traditional system. Tariff evaluation using a 20% target margin showed that 79 drugs exhibited a positive tariff deviation and 21 drugs exhibited a negative tariff deviation relative to the ABC-based proposed tariff. These findings indicate that ABC strengthens pharmacy cost information, supports the evaluation of actual margins, and provides a basis for prioritizing drug-tariff review. The managerial implications include strengthening the hospital's Unit Cost Team, improving the recording of pharmacy activities, integrating pharmacy data systems, and conducting periodic tariff evaluation based on activity costs and actual margins.